Pengaruh Marketing Mix terhadap Re-Visit Intention Melalui Patient Satisfaction pada Rumah Sakit Ibu dan Anak (RSIA) Di Kota Batam - Syukriansyah, Azizul; Kesumahati, Erilia (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study aims to determine and analyze the effect of marketing mix on re-visit intention of patients at Mother and Child Hospitals in Batam City through patient satisfaction. The sample used in this study was 340 people. The results of the study showed that the product and promotion variabels, people did not have a significant positive effect on patient satisfaction. price, place, process, physical evidence variabels had a significant positive effect on patient satisfaction. The results study also show that the product, promotion, and people variabels did not have a significant positive effect on re-visit intention through patient satisfaction. While the price, place, process, physical evidence variabels have a significant positive effect on re-visit intention through patient satisfaction. In addition, patient satisfaction has a significant positive effect on re-visit intention. Mother and Child Hospitals) must be able to adapt the marketing mix in carrying out services to patients, in order to provide good and excellent service.